A Public Health Approach to Child Protection: Why Data Matter. (3rd November 2014) - Broadley, Karen; Goddard, Chris
<x content-type="archive" xml:space="preserve">Abstract</x> In Australia, many researchers and policy makers believe that statutory child protection systems are overburdened and ineffective. The way forward, they suggest, is a public health model of child protection. A public health approach comprises four steps: (1) collecting surveillance data; (2) establishing causes and correlations; (3) developing and evaluating interventions; and (4) disseminating information about the effectiveness of intervention activities to the public health community. However, in Australia there are no reliable surveillance data. There is no information about 'person'. Information is not collected about the characteristics of children (e.g., ethnicity) and parents (e.g., mental illness) reported to child protection services. Data are not comparable across place. This is because the states and territories have their own child protection legislation, definitions and data recording methods. Data are not comparable over time. This is because many jurisdictions have introduced new data recording systems over recent years. This paper concludes that it is essential to develop an effective child protection surveillance data system. This will ensure that services are located in areas and targeted towards populations in greatest need. It will enable large-scale evaluation of the effectiveness of prevention and intervention activities.